Alternative pacing strategies for optimal cardiac resynchronization therapy - Hua, Juan; Kong, Qiling; Chen, Qi (Frontiers in Cardiovascular Medicine, 2022)
Cardiac resynchronization therapy (CRT) via biventricular pacing (BVP) improves morbidity, mortality, and quality of life, especially in subsets of patients with impaired cardiac function and wide QRS. However, the rate of unsuccessful or complicated left ventricular (LV) lead placement through coronary sinus is 5–7%, and the rate of “CRT non-response” is approximately 30%. These reasons have pushed physicians and engineers to collaborate to overcome the challenges of LV lead implantation. Thus, various alternatives to BVP have been proposed to improve CRT effectiveness. His bundle pacing (HBP) has been increasingly used by activating the His–Purkinje system but is constrained by challenging implantation, low success rates, high and often unstable thresholds, and low perception. Therefore, the concept of pacing a specialized conduction system distal to the His bundle to bypass the block region was proposed. Multiple clinical studies have demonstrated that left bundle branch area pacing (LBBAP) has comparable electrical resynchronization with HBP but is superior in terms of simpler operation, higher success rates, lower and stable capture thresholds, and higher perception. Despite their well-demonstrated effectiveness, the transvenous lead-related complications remain major limitations. Recently, leadless LV pacing has been developed and demonstrated effective for these challenging patient cohorts. This article focuses on the current state and latest progress in HBP, LBBAP, and leadless LV pacing as alternatives for failed or non-responsive conventional CRT as well as their limits and prospects.